2015
DOI: 10.1210/jc.2014-4434
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Replacement in Androgen-Deficient Men With Ejaculatory Dysfunction: A Randomized Controlled Trial

Abstract: T replacement was not associated with significant improvement in EjD in androgen-deficient men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 37 publications
1
34
0
1
Order By: Relevance
“…Accordingly, a higher prevalence of hypogonadism was observed in patients with PEVR compared with the rest of the sample without hypogonadism (9.1% vs. 5.3%; P<0.05 after adjustment for age, BMI and smoking habits). Conversely, in a double-blind, randomized, placebo-controlled, 16-week trial with T solution 2% versus placebo (36), T replacement was not associated with significant improvement in ejaculatory dysfunction in androgen-deficient men. Interestingly, the same authors (16) always showed that high T levels increased the odds of DE.…”
Section: Hormonal Regulation Of Ejaculation Functionmentioning
confidence: 94%
“…Accordingly, a higher prevalence of hypogonadism was observed in patients with PEVR compared with the rest of the sample without hypogonadism (9.1% vs. 5.3%; P<0.05 after adjustment for age, BMI and smoking habits). Conversely, in a double-blind, randomized, placebo-controlled, 16-week trial with T solution 2% versus placebo (36), T replacement was not associated with significant improvement in ejaculatory dysfunction in androgen-deficient men. Interestingly, the same authors (16) always showed that high T levels increased the odds of DE.…”
Section: Hormonal Regulation Of Ejaculation Functionmentioning
confidence: 94%
“…Out of 284 retrieved articles, 14 were included in the study [24][25][26][27][28][29][30][31][32][33][34][35][36][37]. However, one study [24] not adequately reporting p values or mean differences was used only when standardized effect size calculations (standardized difference in means [SDM]) were performed.…”
Section: Studies Characteristicsmentioning
confidence: 99%
“…However, one study [24] not adequately reporting p values or mean differences was used only when standardized effect size calculations (standardized difference in means [SDM]) were performed. In addition, in one study [35] only IIEF orgasmic domain was analyzed (Table 1). Available RCTs enrolled 2298 patients, with a mean follow-up of 40.1 wk.…”
Section: Studies Characteristicsmentioning
confidence: 99%
“…Moreover, voiding symptoms and urinary flow rates were equivalent between the two arms over the duration of the study. Three very recent double-blind, placebo-controlled studies performed on 732 hypogonadal men each failed to identify a clinically and statistically significant relationship between TTh and LUTS compared to placebo [1517]. …”
Section: Testosterone and Bphmentioning
confidence: 99%